“Implementación de una secadora cilíndrica a gas para el secado de cacao” - Albán Rocha, Luis David (2023)
At the country level, a large percentage of cocoa farmers and directly small cocoa producers use different natural drying processes that do not guarantee drying times, occupying extended days to extract the cocoa, this means that the process is not continuous since they prefer to sell it in baba not having profitability, so the need arises to design and build a cylindrical cocoa dryer that allows reducing drying times and guarantees affordable costs for the assembly of the machine, so we proceed to investigate the factors involved in cocoa drying.